Telehealth Blood Pressure Monitoring Models In Hypertensive Patients: A Scoping Review - Ahmad Ihsan Fathurrizki; Adinda Putri Lestari; Wafiq Nurul Azizah; Eka Afrima Sari (Journal of Nursing Care, 2022)
The main global cause of death in the world is non-communicable diseases (NCDs). One of NCD is hypertension. Increased hypertension during the Covid-19 pandemic is associated with risk factors for lifestyle changes, social restrictions, lack of physical activity, and stress. Therefore, a remote blood pressure control system is needed to monitor the patient’s health status. The purpose of writing this literature review is to provide an overview of health care practices with remote monitoring of blood pressure of hypertension patients based on online management with telemonitoring. the method used is scoping review with the inclusion criteria of articles were published from 2017 – 2021, used the research designs of Randomized Control Trial and Study Experimental, and were published in English and Indonesian. Articles selections were using PRISMA Flow Diagram 2009 and selection for eligibility were using. The Joanna Briggs Institute Critical Appraisal. Four articles were included in the study and 1037 articles were excluded from the study. It was found that telehealth blood pressure monitoring carried out in hypertensive patients was home and online blood pressure management, TASMINH (Telemonitoring and Self-Management in the Control of Hypertension), and scale-up blood pressure. Telemonitoring was found to be significant in reducing and monitoring patients with home care-based hypertension Self-Monitoring Blood Pressure (SMBP) at home using a digital sphygmomanometer accompanied by direct monitoring of doctors and nurses via the internet can be a solution for monitoring blood pressure during a pandemic.